PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS KEARIFAN LOKAL PALEMBANG PADA SUBTEMA MANUSIA DAN LINGKUNGAN KELAS V SD - Lisdiyanti; Effendi, Darwin; Lia, Linda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims For the purpose of producing instructional films that center on genuine aspects of the Palembang culture and for the purpose of gaining an understanding of the impact that students have on video production applications. In the course of this investigation, the Four D's paradigm, which is often used in developmental studies, is utilized. The students that are taking part in this study are students from SD Negeri 143 Palembang who are in the fifth grade. A very valid rating of 88% has been awarded to the local wisdom learning film from Palembang that was directed at the fifth grade of primary school students and focused on the subject of people and humanity. During the course of the product testing period, a survey was administered to 93 percent of the participants in order to determine the extent to which they were engaged with the product. As a result, the local wisdom learning video that was created for fifth graders in Palembang and focused on the topic of people and their environment is genuine and has received some great responses. When it comes to instructional objectives, this movie is perfect.